Family Suppot as a Determinant of Quality of Life Among Patients with Hypertension in an Internal Medicine Outpatient Clinic - Adywaluya Waluya (Journal of health research and technology, 2026)
Introduction: Hypertension is a global health problem with a prevalence of approximately 1.28 billion people (26.4% of the world's population). This condition is characterized by blood pressure above normal and can reduce quality of life. Family support is believed to play an important role in improving the quality of life of hypertensive patients. This study aims to analyze the relationship between family support and quality of life of hypertensive patients in the Internal Medicine Clinic of Palabuhan Ratu Regional Hospital, Sukabumi Regency. Methods: The study design used a cross-sectional correlational approach with a population of 277 patients and a sample of 164 respondents through accidental sampling technique. Instruments study is questionnaire Family Support Scale (FSS) and WHOQOL-BREF. Data analysis was carried out in a way univariate and bivariate using the Chi-Square test . Results: The results show majority respondents get support family support (81.1%) and have quality life good (89.6%). The Chi-Square test yielded a p-value of 0.000 with an OR of 8.571, indicating a significant relationship between family support and quality of life. Patients with family support were 8.6 times more likely to have a quality life than those without support . Conclusion: This study emphasizes the importance of health promotion, counseling, and education programs involving families so that emotional, informational, instrumental, and reward support can be provided optimally.